KEBIJAKAN FISKAL EKONOMI ISLAM - MUHAMMAD HERU; RAHMI ATIKAH; . NURLAILA (LP2MTBM MAKARIOZ, 2022)
Fiscal policy is a policy taken by the government to spend its income to achieve its economic goals. Fiscal policy has two ways. The first is the income policy which is reflected in the tax policy, and the second is the expenditure policy. According to Islamic economics, fiscal policy is expected to serve the functions of allocation, distribution and stabilization in countries with special characteristics from the value-oriented, ethical and social aspects of the balance of the Islamic state. The sources of acceptance at the time of the Prophet are divided into three main groups. That is, from Muslims, non-Muslims, and other sources. In terms of budget, in the Islamic financial system, government revenues are Zakart, Karaj (agricultural tax), Jizyah (personal tax), Humus (shoes tax), Ushur (business tax), and Carrara heir (no heir). , Kaffarat (fines), grants, and other income from legitimate business. Regarding the mechanism for using the funds, there are products related to the use of these funds. Zakat, and some are not bound. In terms of state budget policies, there are fundamental differences between Islam and modern budget systems. Islam focuses on the issue of serving the affairs of the Ummah. It is presented according to syara' and is determined according to the Islamic point of view. In contrast, modern budgets emphasize a complex combination of planning and projects.